GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.

N-cadherin regulates beta-catenin signal and its misexpression perturbs commissural axon projection in the developing chicken spinal cord - Ciqing Yang; Xiaoying Li; Congrui Wang; Sulei Fu; Han Li; Zhikun Guo; Shanting Zhao; Juntang Lin (Journal of Molecular Histology, 2016)

Removal of polybrominated diphenyl ethers by biomass carbon-supported nanoscale zerovalent iron particles: influencing factors, kinetics, and mechanism - Rongbing Fu; Zhen Xu; Lin Peng; Dongsu Bi (Environmental Science and Pollution Research, 2016)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

Dynamic soil-tunnel interaction in layered half-space for incident plane SH waves - Jia Fu; Jianwen Liang; Lin Qin (Earthquake Engineering and Engineering Vibration, 2016)

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21 - Shuna Fu; Fan Wang; Hongyu Li; Yixuan Bao; Yu Yang; Huifang Shen; Birun Lin; Guangxiong Zhou (Natural Product Research, 2016)

Modeling daily reference ET in the karst area of northwest Guangxi (China) using gene expression programming (GEP) and artificial neural network (ANN) - Sheng Wang; Zhi-yong Fu; Hong-song Chen; Yun-peng Nie; Ke-lin Wang (Theoretical and Applied Climatology, 2016)

Optimal Subdivision for Treatment and Management of Catastrophic Landslides in a Watershed Using Topographic Factors - Chao-Yuan Lin; Kuei-Lin Fu; Cheng-Yu Lin (Environmental Management, 2016)

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Down-regulation of miR-181a can reduce heat stress damage in PBMCs of Holstein cows - Kun-Lin Chen; Yuan-Yuan Fu; Min-Yan Shi; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Lack of association between rs10491334 in the CAMK4 gene and longevity in a Chinese population - RONG LIN; YUNXIA ZHANG; DONGJING YAN; XIAOPING LIAO; YUNXIN FU; WANGWEI CAI (Journal of Genetics, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Bioethanol production by heterologous expression of two individual 1-FEH genes from Helianthus tuberosus in Saccharomyces cerevisiae 6525 - Xi Zhang; Huanhuan Xu; Ruixin Fu; Lijin Jin; Haiyan Zhao; Lin Wang; Mingxiang Liang (BioEnergy Research, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Factorial Analysis of Variables Influencing Mechanical Characteristics in Le Fort I Osteotomy Using FEA and Statistics-Based Taguchi Method - Shao-Fu Huang; Lun-Jou Lo; Chun-Li Lin (Journal of Medical and Biological Engineering, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Soil nutrient variance by slope position in a Mollisol farmland area of Northeast China - Shaoliang Zhang; Lili Jiang; Xiaobing Liu; Xingyi Zhang; Shicong Fu; Lin Dai (Chinese Geographical Science, 2016)

Radial propagation of magnetospheric substorm-injected energetic electrons observed using a BD-IES instrument and Van Allen Probes - QiuGang Zong; YiXin Hao; Hong Zou; SuiYan Fu; XuZhi Zhou; Jie Ren; LingHua Wang; ChongJing Yuan; ZhiYang Liu; XiangHong Jia; Lin Quan; Ying Liu; et al. (Science China Earth Sciences, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

The adipokine Chemerin induces lipolysis and adipogenesis in bovine intramuscular adipocytes - Yuan-Yuan Fu; Kun-Lin Chen; Hui-Xia Li; Guang-Hong Zhou (Molecular and Cellular Biochemistry, 2016)

Cyanidin-3-O-glucoside Induces Apoptosis and Inhibits Migration of Tumor Necrosis Factor-α-Treated Rat Aortic Smooth Muscle Cells - Xuerui Yan; Lin Wu; Bin Li; Xianjun Meng; Hanping Dai; Yanan Zheng; Junfan Fu (Cardiovascular Toxicology, 2016)

Performance comparison of permafrost models in Wudaoliang Basin, Qinghai-Tibet Plateau, China - Guo-an Yin; Fu-jun Niu; Zhan-ju Lin; Jing Luo; Ming-hao Liu (Journal of Mountain Science, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China - Qin-Bo Cheng; Christian Reinhardt-Imjela; Xi Chen; Achim Schulte; Xiang Ji; Fu-Lin Li (Hydrological Sciences Journal, 2016)

Silicon Alleviates Cadmium Toxicity in Two Cypress Varieties by Strengthening the Exodermis Tissues and Stimulating Phenolic Exudation of Roots - Bin Guo; Chen Liu; Nengfei Ding; Qinglin Fu; Yicheng Lin; Hua Li; Ningyu Li (Journal of Plant Growth Regulation, 2016)

Occurrence, spatial distribution, sources, and risks of polychlorinated biphenyls and heavy metals in surface sediments from a large eutrophic Chinese lake (Lake Chaohu) - Wei He; Ze-Lin Bai; Wen-Xiu Liu; Xiang-Zhen Kong; Bin Yang; Chen Yang; Sven Erik Jørgensen; Fu-Liu Xu (Environmental Science and Pollution Research, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Palaeoproterozoic A-type magmatism in northern Wuyishan terrane, Southeast China: petrogenesis and tectonic implications - Zhi-Hong Chen; Guang-Fu Xing; Xi-Lin Zhao (International Geology Review, 2016)

Impact of previous one-step variation in positively long-range correlated processes - Zuntao Fu; Fenghua Xie; Naiming Yuan; Lin Piao (Theoretical and Applied Climatology, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Diversity of phototrophic phytoplankton in Northern South China Sea indicated by rbcL analysis - Nan Li; Shu-Xian Yu; Yin-Chu Wang; Jia-Lin Li; Fu-Chao Li; Song Qin (Journal of Applied Phycology, 2016)

New Re-Os isotopic constrains on the formation of the metalliferous deposits of the Lower Cambrian Niutitang formation - Yong Fu; Lin Dong; Chao Li; Wenjun Qu; Haoxiang Pei; Wenlang Qiao; Bing Shen (Journal of Earth Science, 2016)

Application of the non-seismic geophysical method in the deep geological structure study of Benxi-Huanren area - Chong Peng; Lin-Fu Xue; Zheng-Hong Liu; Hai-Yan Liu (Arabian Journal of Geosciences, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Pseudoginsenoside-F11 inhibits methamphetamine-induced behaviors by regulating dopaminergic and GABAergic neurons in the nucleus accumbens - Kequan Fu; Huiyang Lin; Yoshiaki Miyamoto; Chunfu Wu; Jingyu Yang; Kyosuke Uno; Atsumi Nitta (Psychopharmacology, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Characteristics Analyses and Comparisons of the Protein Structure Networks Constructed by Different Methods - Shangli Cheng; Hua-Lin Fu; Da-Xiang Cui (Interdisciplinary Sciences: Computational Life Sciences, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Changes of lead speciation and microbial toxicity in soil treated with repeated Pb exposure in the presence of BDE209 - Rong Zhang; Wei Zhang; Gao Liu; Kuangfei Lin; Rongbing Fu (Environmental Science and Pollution Research, 2016)

OsBAK1 is involved in rice resistance to Xanthomonas oryzae pv. oryzae PXO99 - Hualan Liao; Xiaorong Xiao; Xiuqiong Li; Yan Chen; Xiumei Fu; Daozhe Lin; Xiaolei Niu; Yinhua Chen; Chaozu He (Plant Biotechnology Reports, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Early Life Exposure to Ractopamine Causes Endocrine-Disrupting Effects in Japanese Medaka (Oryzias latipes) - Liwei Sun; Sisi Wang; Xia Lin; Hana Tan; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Metabolic differences of industrial acarbose-producing Actinoplanes sp. A56 under various osmolality levels - Kun-tai Li; Wei-fu Peng; Wei Xia; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2016)

Time irreversibility of mean temperature anomaly variations over China - Fenghua Xie; Zuntao Fu; Lin Piao; Jiangyu Mao (Theoretical and Applied Climatology, 2016)

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy - Weiwei Yuan; Chunmei Tang; Wensi Zhu; Jiening Zhu; Qiuxiong Lin; Yongheng Fu; Chunyu Deng; Yumei Xue; Min Yang; Shulin Wu; Zhixin Shan (Molecular and Cellular Biochemistry, 2016)

Smad signal pathway regulates angiogenesis via endothelial cell in an adipose-derived stromal cell/endothelial cell co-culture, 3D gel model - Shiyu Lin; Jing Xie; Tao Gong; Sirong Shi; Tao Zhang; Na Fu; Yunfeng Lin (Molecular and Cellular Biochemistry, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)